Interprofessional Paediatric High-Fidelity Simulation Training: A Mixed Methods Study of Experiences and Readiness among Nursing and Medical Students - Helmut Beichler; Simone Grandy; Silke Neumaier; Anneliese Lilgenau; Hannah Schwarz; Michael Wagner (MDPI AG, 2024)
Background: Training in communication skills between nursing and medical students during interprofessional paediatric emergency simulation training represents a significant aspect of safe patient care. Evidence highlights that poor communication in paediatric emergency scenarios jeopardises patient safety. Through realistic simulations, students practice the communication strategies of crisis resource management (CRM), such as "closed-loop communication", "speaking up", and "team time-out". Aims: In this study, we aimed to evaluate the impact of interprofessional simulation on enhancing teamwork and communication skills. Additionally, we sought to assess the occurrence of contexts for the three CRM communication strategies during simulations. Methods: Employing a mixed methods research design, the analysed students completed pre- and post-simulation online questionnaires. To measure attitudes towards interprofessional collaboration, we used the German version of the University of West England Interprofessional Questionnaire (UWE-IP_german), and to measure interprofessional attitudes, we used the Greifswald Questionnaire for the Measurement of Interprofessional Attitudes (Greif Mie), also in German, for both pre- and post-simulation. For qualitative video analysis, we utilised Grounded Theory Methodology (GTM). Results: Following simulation training, we observed a significant improvement (p > 0.001) in the subscale "attitude towards interprofessional learning" of the UWE-IP_german among nursing and medical students. Medical students consistently exhibited a significantly (p < 0.001) more positive attitude towards other professionals in both the pre- and post-simulation assessments. Overall, all the students expressed satisfaction with the interprofessional simulation training. In the qualitative selective coding process, the central phenomenon "participation" could be identified in the coding paradigm. Conclusion: This study presents substantial evidence of the learning impact of interprofessional paediatric simulation training on nursing and medical students.